Sustainable approach for wastewater treatment using microbial fuel cells and green energy generation – A comprehensive review - Khandaker, S.; Das, S.; Hossain, M.T.; Islam, A.; Miah, M.R.; Awual, Rabiul (ELSEVIER, 2021)
This review was represented the recent progress in Microbial Fuel Cells (MFCs) for eco-friendly and sustainable wastewater treatment technology with numerous analysis, laboratory and industrial-scale applications. Due to the several limitations of the conventional wastewater treatment, the sustainable applications of MFCs could be a viable alternative in the wastewater treatment, bio-electricity generation, bio-hydrogen production, carbon sequestration and eco-friendly solution to effluent treatment. This fuel cell offered the carbon neutral wastewater treatment and the degradation of organics components by deploying different kinds of microbes to transform chemical energy into electricity. The electrochemical mechanism was depended on an anodic oxidation and cathodic reduction process, which was significantly improved by the extensive research over the past few decades. An electricity generation from wastewater employing the MFCs was reduced environmental pollution and fossil fuel depletion problems. In this review, the principal challenges were outlined followed by proposed emerging solutions based on electricity generation in tandem with wastewater treatment. Furthermore, the operational efficiency of MFCs, potentials, and emerging scope of future research was demonstrated. The possible inclusion of MFCs in integrated energy generation systems for wastewater treatment was investigated from recant literature overview for their potential commercialization.